Measuring Patient-Reported Outcomes in Rhinoplasty Using the FACE-Q: A Single Site Study - East, Charles; Badia, Lydia; Marsh, Daniel; Pusic, Andrea; Klassen, Anne F. (Facial Plastic Surgery, 2017)
Rhinoplasty is one of the most popular surgical cosmetic treatments. Measuring the appearance of the nose has typically involved the use of observer- or surgeon-reported outcome measures (e.g., photographs). While objective outcomes are important, facial appearance is subjective, and therefore outcome assessment should incorporate the patient perspective through the use of patient-reported outcome measures. This study aims to explore relationships between FACE-Q scales scores and measuring adverse effects and change 4 months after surgery in a United Kingdom sample. A questionnaire booklet was completed by patients seeking rhinoplasty between March 2014 and March 2015. The study was conducted at a facial plastic surgery clinic office in London, United Kingdom. Pre- and postoperative rhinoplasty patients aged 19 years and older participated in the study. FACE-Q scales/checklist was utilized for the study. A total of 54 preoperative patients completed seven FACE-Q scales. Before surgery, characteristics of the nose that our sample at least satisfied (i.e., at the harder end of the clinical hierarchy) included the tip of the nose, and how the nose looked in photos and from different angles. In preoperative participants, lower scores for satisfaction with nose and/or nostrils correlated with lower satisfaction with facial appearance and appearance-related psychosocial distress. Participants (N = 13) who had surgery reported significant improvement in satisfaction with the nose, nostrils, and facial appearance overall, and improved psychological and social function. Standardized response means ranged from 0.65 (social function) to 1.55 (facial appearance). The FACE-Q rhinoplasty module can be used in clinical practice, research, and quality improvement to incorporate the patient perspective of appearance in outcome assessments. The level of evidence is defined as level III (diagnostic).
Keywords: rhinoplasty; patient-reported outcome; clinical practice; research